PRELIMINARY CONSIDERATIONS ABOUT CHILDREN IN NEED OF SPECIAL HELP - Kalykbayeva Almagul; Rakhimova Khurshidakhan Sadikovna (Academia Science Repository, 2023)
This article presents early views of children with special needs and views of people with disabilities by scholars.